2012
DOI: 10.1097/id.0b013e3182563e0d
|View full text |Cite
|
Sign up to set email alerts
|

Nonprocessed Adipose Tissue Graft in the Treatment of Dehiscence Bone Defects in Rabbit Tibiae

Abstract: Nonprocessed adipose tissue is not a comparable substitute for autogenous bone in the treatment of dehiscence bone defects around titanium dental implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…In contrast to the present results, Matsubara et al (14) demonstrated that non-processed adipose tissue is not an adequate substitute for autogenous bone in the treatment in dehiscent bone defects surrounding implants. This important difference among the results occurred possibly because those authors did not macerate the tissue.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to the present results, Matsubara et al (14) demonstrated that non-processed adipose tissue is not an adequate substitute for autogenous bone in the treatment in dehiscent bone defects surrounding implants. This important difference among the results occurred possibly because those authors did not macerate the tissue.…”
Section: Discussioncontrasting
confidence: 99%
“…Recent histological studies (12,13) reported that macerated adipose tissue might favor bone repair when applied to craniofacial defects. On the other hand, Matsubara et al (14) reported the use of adipose tissue graft to treat peri-implant dehiscence, indicating that the presence of adipose tissue could act as a barrier for new bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…Despite all advances in the use of stem cells derived from adipose tissue for the repair of bone defects, there are few studies in the literature that used autogenous adipose tissue as a grafting material for the treatment of maxillary (13,14) and cranial bone defects (15). Matsubara et al (14) also observed that the use of adipose tissue graft did not favor the repair of dehiscence bone defects created surgically in dental implants placed in rabbit tibiae.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it is hypothesized that the use of immediate transplant using fragmented subcutaneous white adipose tissue could be a plausible alternative for the treatment of bone deformities (Gomes et al, 2012; Matsubara et al, 2012). Biologically, the premise that the adipose tissue could be used as a regenerative biomaterial is due to the significant presence of stem cells in it (2500-fold more than the frequency of stem cells in bone marrow [Fraser et al, 2008]), which in theory may originate higher quantities of differentiated cells, including osteoblasts (Fraser et al, 2006; Helder et al, 2007).…”
mentioning
confidence: 99%